106 Virtual-PCI With iFR-Pullback can Plan Coronary Intervention in Complex Coronary Disease with a Prediction of Functional Gain. (6th June 2015) - Nijjer, Sukhjinder; Sen, Sayan; Davies, Justin; Petraco, Ricardo; Al-Lamee, Rasha; Broyd, Christopher; Mikhail, Ghada; Malik, Iqbal; Mayet, Jamil; Francis, Darrel
Abstract : Background: Coronary intervention is increasingly performed in complex and tandem coronary disease where physiological optimisation is less practical. Advances in computation allow physiological maps of stenosis-specific coronary pressure loss to be mapped upon angiographic images. Virtual-PCI conceptually allows selective removal of a stenosis and predict the functional gain of a given stenting strategy. We sought to assess the change in resting haemodynamics after intervention and the feasibility of Virtual-PCI to predict post-PCI iFR. Method: Pressure and flow velocity measurements were made before and after PCI to 75 stenoses. Data was used to model the change in pressure ratios after PCI. Intracoronary motorised pressure-wire iFR-pullbacks were performed at rest in a separate cohort of 32 coronary arteries with tandem and diffuse disease to iFR changes onto the angiogram. Virtual-PCI predicted a post-PCI iFR (iFRpredicted ) assuming the perfect removal of a given stenosis (Figure 1 ). This was compared to the observed iFR post real-world PCI (iFRobserved ). Results: Resting flow velocity over the wave-free period changed by only 4.4 cm/s; a demonstrable change was noted when stenoses had pre-PCI FFR <0.60 but trivial change (1.3 cm/s) in moderate stenoses. In contrast, pressure gradients and ratios rose after PCI without a change in flow suggesting the interaction between stenoses at rest is minimal. In the tandem disease cohort, mean vessel iFR pre-PCI was 0.78 ± 0.03. Virtual PCI predicted an iFRexpected of 0.94 ± 0.01. The observed iFR after real-world PCI was iFRobserved 0.93 ± 0.01 with no significant difference between the predicted and observed increase (ΔiFRexpected :0.16 ± 0.03 vs ΔiFRobserved 0.13 ± 0.03 p = 0.48). No significant systematic bias between iFRexpected and iFRobserved was noted (Bland-Altman mean difference 0.016 ± 0.004). Conclusions: Virtual-PCI enables selective removal a stenosis from an iFR-pullback physiological map of the vessel and predict the haemodynamic effect of that chosen intervention. The post-PCI physiological result can be predicted without systematic bias permitting virtual assessment of the functional gain of different stenting strategies. Virtual-PCI using iFR-Pullback is feasible in the catheter laboratory and real-time algorithms may enable live co-registration with the angiogram to make an advance in how intervention is performed in the future.